2013
DOI: 10.1007/s13277-013-1150-z
|View full text |Cite
|
Sign up to set email alerts
|

CIP2A is overexpressed in osteosarcoma and regulates cell proliferation and invasion

Abstract: Cancerous inhibitor of protein phosphatase 2A (CIP2A) is a newly characterized oncoprotein involved in a variety of malignant tumors. However, its expression pattern and biological functions in osteosarcoma remain unclear. In the present study, CIP2A expression was analyzed in 51 human osteosarcoma specimens using immunohistochemistry. CIP2A siRNA was used in the MG-63 cell line, and the effect of CIP2A depletion on cell proliferation and invasion was evaluated. We found that CIP2A was overexpressed in 76.5 % … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 38 publications
3
12
0
Order By: Relevance
“…In a cell model, invasion and epithelial–mesenchymal transition were found to be associated with CIP2A expression . Therefore, high CIP2A expression was also found to be a poor prognostic factor in patients with many different types of cancer, including lung, breast, gastric, gall bladder, brain, prostate, and skin cancer . Our results are consistent with those of other studies showing that high CIP2A expression is associated with a poor prognosis in patients with PTC.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In a cell model, invasion and epithelial–mesenchymal transition were found to be associated with CIP2A expression . Therefore, high CIP2A expression was also found to be a poor prognostic factor in patients with many different types of cancer, including lung, breast, gastric, gall bladder, brain, prostate, and skin cancer . Our results are consistent with those of other studies showing that high CIP2A expression is associated with a poor prognosis in patients with PTC.…”
Section: Discussionsupporting
confidence: 91%
“…CIP2A localizes in the cytoplasm and may interact with DAPK to prevent apoptosis . Therefore, the IHC expression pattern of CIP2A is entirely cytoplasmic in both benign and malignant thyroid tumors, which is consistent with its expression patterns in other malignancies . Overexpression of CIP2A increases cancer aggressiveness .…”
Section: Discussionsupporting
confidence: 66%
“…In addition, it has been reported that CIP2A immunostaining level positively correlated with metastasis in renal cell carcinomas (6). More recently, In addition, Zhai et al (20) found that CIP2A was overexpressed in osteosarcoma tissues, and that CIP2A depletion attenuated cell proliferation and invasion. In addition, CIP2A depletion inhibited matrix metalloproteinases-9 (MMP-9) mRNA expression.…”
Section: A B C Discussionmentioning
confidence: 97%
“…Furthermore, CIP2A activates multiple oncogenic proteins, including protein kinase B (Akt), c‐Myc, E2F transcription factor 1 (E2F1), polo‐like kinase 1 (Plk1), and mammalian target of rapamycin complex 1 (mTORC1), in various cancers and promotes the proliferation of cancer cells. In addition, the overexpression of CIP2A reported in several common cancers is associated with poor prognosis . Recent reports have suggested that CIP2A is a potential target for anticancer drugs in several cancers and its inhibition was shown to reduce tumor formation in various cancer models .…”
Section: Introductionmentioning
confidence: 99%